The effect of the number of open vertebral segments on the prognosis of newborns with midline closure defect: A single surgeon, single center experience - Çetinkal, Ahmet; Tahta, Alican (Turkish Neurosurgical Society, 2021)
AIM: To investigate the effect of the number of open vertebral segments on the prognosis of newborns with midline closure defects (MCD), and the optimal timing for ventriculoperitoneal shunt (VPS) placement in those with MCD accompanied by hydrocephalus. MATERIAL and METHODS: A total of 63 patients (35 girls and 28 boys) were admitted to the neonatal intensive care unit between April 2016 and January 2019. The patients’ MCDs were examined in terms of type, localization, number of open vertebral segments, accompanying hydrocephalus (HC), surgical technique, and complications. RESULTS: The mean follow-up period was 12 months (6-24 months). Ten cases of meningocele (M) (15.9%), 41 cases of myelomeningocele (MM) (65%), and 12 cases of encephalocele (E) (19.1%) were identified. A VPS was inserted in 44 (69.8%) patients (E, 8; MM, 34; and M, 2), performed in 33 patients during the same admission, while 11 were shunted after discharge during the follow-up period. Thirty-four of the 41 cases of MM and all cases of M and E were primarily closed, while the remaining MMs required skin flaps. The M and MM cases were categorized according to the number of open vertebral segments and examined in CONCLUSION: In all pediatric cases, case-by-case evaluation, attention to hypothermia and meticulous hemostasis, protection of functional neural tissue, closing the defect as soon as possible, and treating accompanying HC during the same session, were tissue density correlated with the number of open vertebral segments and it was considered.
Keywords: Hydrocephalus; Midline Closure Defect; Newborn; Surgical Treatment